Pentraxin-3 concentration in the amniotic fluid of women at term, in spontaneous preterm labor and when not in labor - Martin, Laura F. [UNESP]; Moco, Natalia P. [UNESP]; Ramos, Bruna R. A. [UNESP]; Camargo, Rodrigo P. S.; Silva, Marcia Guimarães da [UNESP] (Elsevier B.V., 2014)
Objective: To evaluate the concentration of PTX3 in amniotic fluid (AF) during the final weeks of normal pregnancies and in pregnancies complicated by preterm delivery (PTD).Study design: A cross-sectional study was conducted with 95 pregnant women followed to term and 25 who presented with PTD. Samples of AF from all patients were obtained during cesarean section and the PTX3 concentration was determined by enzyme immunoassay (ELISA). Maternal characteristics were compared by ANOVA and the Kruskal-Wallis and Chi square tests. Comparison between PTX3 concentrations in the PTD in labor and PTD not in labor groups were performed using the Mann-Whitney test. A p value <0.05 was considered statistically significant.Results: Regarding term pregnancies, PTX3 concentrations were not statistically different across the period studied (37 weeks to 40 weeks). Among preterm pregnancies, those in preterm labor (PTL) presented higher PTX3 levels than those not in labor (p = 0.001) and the risk of occurrence of PTL increased by 1% with a rise of 1 pg/mL in PTX3.Conclusion: PTX3 is a physiological constituent of the AF, and its concentration is elevated in the presence of spontaneous PTL, reinforcing the theory that PTX3 plays a role in the innate immune response during gestational complications associated with infectious/inflammatory conditions. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Inflammation; Innate immunity; Acute phase response; Prematurity